Peripheral inflammation-induced changes in songbird brain gene expression: 3' mRNA transcriptomic approach - Kuttiyarthu Veetil, Nithya; Cedraz de Oliveira, Haniel; Gomez-Samblas, Mercedes; Divín, Daniel; Melepat, Balraj; Voukali, Eleni; Świderská, Zuzana; Krajzingrová, Tereza; Těšický, Martin; Jung, Ferris; Beneš, Vladimír; Madsen, Ole; et al. (Developmental and comparative immunology, 2024)
Species-specific neural inflammation can be induced by profound immune signalling from periphery to brain. Recent advances in transcriptomics offer cost-effective approaches to study this regulation. In a population of captive zebra finch (Taeniopygia guttata), we compare the differential gene expression patterns in lipopolysaccharide (LPS)-triggered peripheral inflammation revealed by RNA-seq and QuantSeq. The RNA-seq approach identified more differentially expressed genes but failed to detect any inflammatory markers. In contrast, QuantSeq results identified specific expression changes in the genes regulating inflammation. Next, we adopted QuantSeq to relate peripheral and brain transcriptomes. We identified subtle changes in the brain gene expression during the peripheral inflammation (e.g. up-regulation in AVD-like and ACOD1 expression) and detected co-structure between the peripheral and brain inflammation. Our results suggest benefits of the 3'end transcriptomics for association studies between peripheral and neural inflammation in genetically heterogeneous models and identify potential targets for the future brain research in birds.
Keywords: mozek; messenger RNA; Inflammation; Songbirds; Avian cytokine; zvířata; zánět; Neurogenic inflammation; RNA, Messenger; Neuroimmune interaction; Brain; stanovení celkové genové exprese; transkriptom; Transcriptome; Differential gene expression; zpěvní ptáci; Animals; Gene Expression Profiling; Finches; Peripheral immunity; pěnkavovití